Digital Literacy Skills and STEM Career Path Choice Intentions among Junior Secondary School Girls in North-Central Nigeria - Iroaganachi, Mercy; Opeke, Rosaline; Babalola, Yemisi; Soyemi, Opeyemi (Covenant Journal of Informatics and Communication Technology, 2021)
Secondary schools girls’ STEM career path choice intentions refers to the girls’ willingness to choose subjects comprising science, technology, engineering and mathematics, which would be required for enrolment into their desired courses of study in higher institutions and eventual career placement in STEM professions. The study investigated digital literacy skills as a determinant of STEM career path choice intentions of secondary school girls in North-Central Nigeria. Survey research design was adopted for the study. The population consisted of 5,433 junior secondary school girls from Federal Government Colleges in the geo-political zone. Multi-stage sampling technique was employed for selecting the sample size of 361 girls. Data collection instrument was a validated questionnaire. Descriptive statistics and binary logistics regression were used for data analyses. Findings showed that GSCPCIs at the junior secondary school level is high. It was also revealed that digital literacy skills can greatly influence girl’s STEM career path choice intentions as components of digital literacy skills such as photo-visual skills predicted GSCPCIs (β = 1.270, p < 0.05) while ICT skills (β = 0.100, p > 0.05), reproduction skills (β = 0.458, p ˃ 0.05), information skills (β = 0.016, p ˃ 0.05) and real-time thinking skills (β = 0.071, p ˃ 0.05) were positively correlated with STEM career part choice intentions of girls. Therefore, the study recommends that trainings on digital literacy skills should be intensified at the secondary school level, especially, for girls among others.